Art-pedagogical aspect of prevention of suicidal behavior among adolescents and youth. (Journal of Educational Sciences, 2016)
The authors examine the art pedagogical methods as the optimal tool in solving the complex problem of suicide among children and adolescents. In their view, art methods (or methods of art pedagogic), as a more public and «lightweight» on the background of art therapy, allow you to work with feelings: to explore and promote them on a symbolic level, to actualize and Express conscious and unconscious feelings and needs, including those which Express with words the teenager is too difficult. Further, the authors, on the basis of the content analysis of publications on the problem under study revealed the presence of phases in the development of the art therapy services and collate all information received data on the experiences of countries in developing national and regional art teaching and art therapy schools. Thus, the authors come to the conclusion that the possibilities of art pedagogic and art therapy in the context of prevention of suicidal behavior and related manifestations are sufficiently large that the use of appropriate methods in mass education will largely be determined by solving the problem of early warning of suicidal tendencies in adolescents and youth in Kazakhstan. The article is written in part by authors of the grant project Ministry of education and science of the Republic of Kazakhstan «The Art pedagogic and art therapy for the prevention of suicidal behavior of youth in Kazakhstan: development of scientific bases and practical techniques.»